LABORATORY MANAGEMENT UPT SFT SMP NEGERI 27 MAKASSAR - Samputri, Salma; Arif, Rifda Nur Hikmahwati; Lilianty, Yuni; Ramadhani, Reski (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research aims to: 1) To find out the management of science laboratories at UPT SPF SMP Negeri 27 Makassar in the planning aspect. 2) To find out the management of science laboratories at UPT SPF SMP Negeri 27 Makassar in the aspect of implementation.3) To find out the management of science laboratories at UPT SPF SMP Negeri 27 Makassar in the evaluation aspect. The type of research in this article is descriptive using a quantitative approach at UPT SPF SMP Negeri 27 Makassar. The population in this study was UPT SPF SMP Negeri 27 Makassar and the sample selected was the laboratory using the saturated sampling method. The research instruments and data collection techniques used were observation sheets. Descriptive statistical analysis is the analysis technique used in this study. The results showed that: on planning indicators, science laboratory management at UPT SPF SMP Negeri 27 Makassar was in the very poor category with a score of 24.24. Meanwhile, the implementation indicator shows that the science laboratory management at UPT SPF SMP Negeri 27 Makassar is in the insufficient category with a score of 35.29. Then, on evaluation indicators, science laboratory management at UPT SPF SMP Negeri 27 Makassar is in the insufficient category with a score of 25.92.